"A part to play": the value of role-play simulation in undergraduate legal education. Issue 2 (3rd May 2016) - Waters, Ben
Abstract : This article explores the argument for increased student participation in experiential learning approaches within the UK undergraduate law curriculum. It is supported by the findings of a very small-scale research study undertaken by the writer into law students' perceptions of the efficacy of role-play simulation as a means of studying mediation, in an optional credit-based module within the final year of a UK undergraduate qualifying law degree. In order to provide situational context, the first part of this article will briefly address the experiential learning possibilities for undergraduate law students, a discussion of the study involving qualitative research methodology, which was used to demonstrate that role-play simulation as a method of experiential learning has a place within the UK undergraduate law curriculum. The final part of this article will consider the findings of the study which demonstrated that, inter alia, role-play simulation can be motivational, helps to build student confidence, enables deeper learning, assists graduate skills acquisition and arguably enhances employability. Based on the findings of this study and other empirical evidence, the article suggests that greater emphasis could be placed on experiential approaches such as role-play simulation for credit-based law courses, including those "core" foundational courses which form part of the undergraduate qualifying law degree in the UK, but achievement of this aspiration is not without its challenges.